Acute Decrease in Flow in the Right Middle Cerebral Artery Detected by Transcranial Doppler Following High-Intensity Transient Signals in a Patient With Carotid Artery Dissection. Issue 2 (June 2019) - Burkman, Marilyn H.; Nicoletto, Heather A.; Loochtan, Aaron I.; Laskowitz, Daniel T.; Dodds, Jodi A.
We report a case of evolving multiple vascular dissections where transcranial Doppler with emboli monitoring provided evidence of hemodynamic compromise after microembolic high-intensity signals suggested a clinical change in a patient presenting with a single left carotid artery dissection and pseudoaneurysm. She initially presented with Horner syndrome and later developed signs of right-sided ischemia on maximal medical therapy necessitating carotid stenting.